Nationality, school and vote: the Liga Nacionalista of São Paulo - Boto, Carlota (Universidade Estadual Paulista / UNESP, 2009)
The purpose of this article is to analyze the pedagogic discourse of the Liga Nacionalista de São Paulo between 1917 and 1922. This political organization was ruled by sectors of the São Paulo's elite, but included also representatives of the midlle classes, state schools' teachers, for instance. In those years, the agenda of activities of the Liga Nacionalista focused on two main reivindications: the secret vote and the expansion of the elementary school.